Aspectele problematice ale separării jurisdicției administrative de alte tipuri de jurisdicții judiciare în Ucraina - Bzova, Laura (Revista Universul Juridic, 2021)
This article examines the procedure for distinguishing administrative jurisdiction from other judicial jurisdictions. Scientific approaches to this issue are analyzed, as well as current case law on the unequal application of current legislation.
Keywords: judicial jurisdiction, administrative jurisdiction, court decisions